2021
DOI: 10.2196/23481
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Use of the Care Information Exchange Portal: Cross-sectional Study

Abstract: Background Sharing electronic health records with patients has been shown to improve patient safety and quality of care. Patient portals represent a convenient tool to enhance patient access to their own health care data. However, the success of portals will only be possible through sustained adoption by its end users: the patients. A better understanding of the characteristics of users and nonusers is critical for understanding which groups remain excluded from using such tools. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…Equitable patient involvement in error surveillance is, on a basic level, contingent on all patients being able to access and understand PHR information. The characteristics of our sample are consistent with those of previous studies, reinforcing a distinct demographic profile associated with portal use, with users tending to be female, older, highly educated, with higher digital health literacy [ 14 , 22 , 23 , 41 ]. Previous studies have demonstrated that patients who struggle to use web-based information for health purposes are less likely to use PHR systems and that lacking these eHealth literacy skills may contribute to adverse health outcomes [ 23 , 42 - 44 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Equitable patient involvement in error surveillance is, on a basic level, contingent on all patients being able to access and understand PHR information. The characteristics of our sample are consistent with those of previous studies, reinforcing a distinct demographic profile associated with portal use, with users tending to be female, older, highly educated, with higher digital health literacy [ 14 , 22 , 23 , 41 ]. Previous studies have demonstrated that patients who struggle to use web-based information for health purposes are less likely to use PHR systems and that lacking these eHealth literacy skills may contribute to adverse health outcomes [ 23 , 42 - 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…The characteristics of our sample are consistent with those of previous studies, reinforcing a distinct demographic profile associated with portal use, with users tending to be female, older, highly educated, with higher digital health literacy [ 14 , 22 , 23 , 41 ]. Previous studies have demonstrated that patients who struggle to use web-based information for health purposes are less likely to use PHR systems and that lacking these eHealth literacy skills may contribute to adverse health outcomes [ 23 , 42 - 44 ]. Our analysis reveals that patients with lower digital health literacy are also less likely to understand the information held in the PHR, which may partly explain the health disparities observed in this patient group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Equally, special attention must be paid to disparities in access and use of electronic health records by low-income, racial and ethnic minorities, lower literate and linguistically diverse populations [ 12 ]. Recently, we have evaluated the determinants of usage of the Care Information Exchange (the largest shared patient portal programme in the UK, hosting the records of over 2.3 million people living in North West London) and observed that individuals with a higher educational degree or higher digital literacy scores had higher odds of being a portal user [ 13 ]. It is critical that further research systematically addresses these inequalities through patient-centred interventions aiming to reduce the digital divide and engage effectively with underserved or excluded groups of patients.…”
Section: Patient Access To Health Recordsmentioning
confidence: 99%